On the macroeconomic and fiscal effects of the Tax Cuts and Jobs Act - Philipp Lieberknecht; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2019)
There is substantial disagreement about the consequences of the Tax Cuts and Jobs Act (TCJA) of 2017, which constitutes the most extensive tax reform in the United States in more than 30 years. Using a large-scale two-country dynamic general equilibrium model with nominal rigidities, the authors find that the TCJA increases GDP by about 2% in the medium-run and by about 2.5% in the long-run. The short-run impact depends crucially on the degree and costs of variable capital utilization, with GDP effects ranging from 1 to 3%. At the same time, the TCJA does not pay for itself. In the analysis, the reform decreases tax revenues and raises the debt-to-GDP ratio by about 15 percentage points in the medium-run until 2025. The show that combining the TCJA with spending cuts can dampen the increase in government indebtedness without reducing its expansionary effect.
urn:nbn:de:hebis:30:3-500552
Keywords: E62; E63; E65; 330; tax reform; corporate taxes; capital taxes; labor income taxes; spending cuts; fiscal stimulus